Diagnosis and treatment of suspected symmetrical peripheral gangrene in a Persian cat with feline infectious peritonitis - Hafizsha , Nabila Latifa; Nurfadhilah , Elvina (ARSHI Veterinary Letters, 2025)
Symmetrical Peripheral Gangrene (SPG) is a rare clinical condition characterized by ischemic damage to symmetrical extremity areas at two or more sites without the presence of larger vessel obstruction or vasculitis. This case report describes a male Persian cat diagnosed with Feline Infectious Peritonitis (FIP) based on serum biochemistry, which on the fourth day of FIP treatment, showed symptoms of left metatarsal edema, coldness, and pale yellowish skin discoloration. Based on clinical symptoms, the cat was diagnosed with suspected SPG. Treatment for the lesions included debridement, antibiotics, anti-inflammatory drugs, diuretics, wound care with nano-silver spray, and supportive vitamins. After treatment, the lesion showed significant improvement on day 14 with visible drying, although complete closure had not yet occurred.